Decreased serum TRAIL is associated with increased mortality in smokers with comorbid emphysema and coronary artery disease. (December 2018) - Ajala, Oluremi; Zhang, Yingze; Gupta, Aman; Bon, Jessica; Sciurba, Frank; Chandra, Divay
Abstract: Background: Smokers are highly susceptible to lung and cardiovascular disease that can reduce their survival. Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) is a protein in the circulation that may suppress vascular and pulmonary inflammation. Therefore, we hypothesized that diminished circulating TRAIL levels would be associated with poor survival in smokers with lung and cardiovascular disease. Methods: Serum TRAIL level was measured by immunoassay in 474 smokers. Coronary atherosclerosis was assessed by coronary artery calcium scoring along with emphysema, lung function, and survival. Results: The 474 smokers were 65.7 ± 6.3 years old and 52.2% male with 55.3 ± 31.5 pack-years of tobacco-exposure. 83 of them died during 3588.2 person-years of follow up. At baseline, lower TRAIL level was associated with more coronary artery calcium (OR = 1.2 per SD, 95%CI 1.1–1.5, p  = 0.02), and with history of myocardial infarction (OR = 2.3 per SD, 95%CI 1.2–4.5, p  = 0.02), angina (OR = 1.6 per SD, 95%CI 1.1–2.6, p  = 0.03), and angioplasty (OR = 1.8 per SD, 95%CI 1.0–3.1, p  = 0.04) in models adjusted for cardiovascular risk-factors, FEV1, and emphysema. Also, lower TRAIL level was associated with emphysema severity independent of demographics and tobacco exposure (β = 0.11 sq. root units, 95% CI 0.01–0.22, p  = 0.03). Further, TRAIL level was lowest in smokers with comorbid emphysema and coronary artery calcification rather than either condition alone. Finally, lower TRAIL level was independently associated with increased mortality in smokers particularly in those with comorbid emphysema and coronary artery calcification (HR = 1.38, 95% CI 1.01–1.90). Conclusions: TRAIL level is reduced in smokers with comorbid emphysema and coronary artery disease, and is associated with reduced survival. Highlights: Reduced serum TRAIL is associated with more coronary artery disease (CAD). Reduced serum TRAIL is associated with increased emphysema. TRAIL level is lowest in smokers with both emphysema and CAD. Reduced serum TRAIL predicts mortality in smokers, particularly those with emphysema and CAD.